2020
DOI: 10.1111/1346-8138.15646
|View full text |Cite
|
Sign up to set email alerts
|

Fatal case of pancreatic panniculitis caused by occult neuroendocrine tumor in the corresponding organ: A case report and review of the published work

Abstract: Pancreatic panniculitis (PP) is a rare clinical variant of subcutaneous fat necrosis, developing in patients with a variety of pancreatic diseases such as acute or chronic pancreatitis, tumors and cysts. The tumor‐associated PP represents a noteworthy skin manifestation of underlying internal malignancies, also known as dermadrome. Among causative pancreatic tumors, acinar cell carcinoma is the most frequent malignancy; however, little is known about how the origin of tumor cells and progression stage of pancr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…1 However, it is extraordinarily associated with pancreatic neuroendocrine tumor (PanNET), with only three of 59 PPP syndrome cases and 14 pancreatic panniculitis (PP) cases caused by PanNET. 1,3 We report a middle-aged woman with PanNETinduced PPP syndrome.…”
mentioning
confidence: 93%
See 4 more Smart Citations
“…1 However, it is extraordinarily associated with pancreatic neuroendocrine tumor (PanNET), with only three of 59 PPP syndrome cases and 14 pancreatic panniculitis (PP) cases caused by PanNET. 1,3 We report a middle-aged woman with PanNETinduced PPP syndrome.…”
mentioning
confidence: 93%
“…4 The average patient reads at grade level 7, and nearly 20% of Americans have difficulty comprehending reading grade level 4 text. [3][4][5] This indicates that currently available online resources for PV and BP are on average at least six reading grades higher than recommended and at least five grades higher than the average patient's reading ability. Remarkably, we found that resources written by medical doctors, and especially by dermatologists, had higher ARGL than those written by non-medical doctors.Limitations of our study included the cross-sectional design and possible multi-rater variability across the different validated readability measures.…”
mentioning
confidence: 95%
See 3 more Smart Citations